Frame Radikalisme, Jihad, Terorisme di Media Online Islam: Studi Kasus Pemberitaan Bom Makassar dan Penyerangan Mabes Polri - Sulistyanto, Ari; Mujab, Saeful; Jamil, Achmad (Jurnal Keamanan Nasional, 2021)
The incident of the suicide bombing in front of the Makassar Cathedral Church and the attack on the National Police Headquarters became news topics that attracted media attention. Each media has a policy in the interpretation scheme to fight for meaning according to the media’s point of view. This study aims to explore the meaning and framing of radicalism, jihad, and terrorism in the suicide bombing in front of the Makassar Cathedral Church and the attack on the National Police Headquarters. A qualitative method with a semantic analysis approach is used to determine the meaning, and a thematic approach in viewing the framing of the formation of radical concepts, jihad, and terrorism. The results showed that Islamic online media in providing meaning and framing did not conceptually and specifically discuss radicalism, jihad, and terrorism. However, they view it as a stigma and a label used in an effort to corner and marginalize Islamic groups. The implications of this research can be used as evaluation material for related parties in overcoming the spread of radicalism, jihad, and terrorism.